Validation of Icelus crassus Andriashev (Cottiformes: Cottidae), described from the Sea of Okhotsk - Chernova, Natalia; Kai, Yoshiaki; Zorina, Anna (Zootaxa, 2025)
The validity of the Stocky Sculpin Icelus crassus Andriashev, described from the Sea of Okhotsk, was confirmed following examination of the type series; the species having been previously considered a synonym of I. ochotensis Schmidt. Although both species belong to the “I. bicornis” (sensu Nelson 1984) species group, having suborbital spines and additional rows of scales on the body absent (excluding dorsal-row and lateral-line scales), and fine marginal serrations on the dorsal-row scales rather than sharp single spines, I. crassus differs from the type series of I. ochotensis in the absence of parietal spines (vs. present), supraorbital cirri present as expanding, distally branched laminae (vs. simple barbels), dorsal scale row incomplete anteriorly (vs. complete, reaching head); and lateral-line scales serrated below each sensory canal pore (vs. embedded in skin below each pore, usually with no more than 1–2 spinules). Meristic characters of I. crassus, similar to other species of the “I. bicornis” group, include 38–41 vertebrae, IX 18–20 dorsal-fin rays, 15 or 16 anal-fin rays, 17–19 pectoral-fin rays, 41–43 lateral-line scales, 25–31 dorsal-line scales, and 10–17 axillary scales. The urogenital papilla is cylindrical (not spatulate), with a short, claw-like terminal appendage. The holotype is found in ZIN collection, No. 21900, adult male TL 106 mm. Icelus crassus has been recorded in the Sea of Okhotsk and Sea of Japan (Strait of Tartary) 97–327 m depth; near bottom, water temperatures range from -0.7°C to 2.15°C.